2003
DOI: 10.1038/sj.onc.1206496
|View full text |Cite
|
Sign up to set email alerts
|

Akt negatively regulates translation of the ternary complex factor Elk-1

Abstract: Cross-talk between signaling pathways plays an important role in regulation of cell growth, differentiation, survival, and death. Here, we show that Akt regulates the Elk-1 transcription factor, independent of its negative regulation of Raf kinases. Using a constitutively active Mek1 to bypass the regulation of Raf by Akt, we find that the Elk-1 and Sap1a proteins are dramatically decreased in the presence of activated Akt. Akt catalytic activity is required. Also, Mek-dependent activation of a TCF (Elk-1/Sap-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Proteins (60 g) were separated by SDS-PAGE and immunoblotted with anti-phospho-ERK and anti-Akt antibody, respectively. regulate the Elk-1 transcription factor by decreasing either its expression (Figueroa and Vojtek, 2003) or its activation (Galetic et al, 2003). Therefore, the critical step for the negative regulation of ERK1/2 by Akt lies between the cytosolic activation of ERK1/2 and its activity on nuclear substrates, such as Elk-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins (60 g) were separated by SDS-PAGE and immunoblotted with anti-phospho-ERK and anti-Akt antibody, respectively. regulate the Elk-1 transcription factor by decreasing either its expression (Figueroa and Vojtek, 2003) or its activation (Galetic et al, 2003). Therefore, the critical step for the negative regulation of ERK1/2 by Akt lies between the cytosolic activation of ERK1/2 and its activity on nuclear substrates, such as Elk-1.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, constitutively active Akt can negatively regulate the Ras/Raf/MEF/ERK1/2 cascade via phosphorylation and inactivation of the kinase Raf , leading to the phenotype modulation of differentiated myotubes (Rommel et al, 1999) or of vascular smooth muscle cells (Reusch et al, 2001). An additional level of interaction between Akt and the ERK1/2 pathway has been reported downstream of Ras, Raf, and MEK that involves the down-regulation of the transcription factor Elk-1 (Figueroa and Vojtek, 2003;Galetic et al, 2003). To date, the molecular mechanisms and the functional cellular consequences of this cross-talk remain poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was reported that AKT negatively regulated ELK-1 expression at the level of translation and that a region within the first 279 nt of the ELK-1 open reading frame (ORF) was necessary and sufficient for this control (13,14). These latter studies were performed using GST–ELK-1 fusion constructs; i.e.…”
Section: Introductionmentioning
confidence: 99%
“…AKT can phosphorylate mTOR, and studies in Drosophila have demonstrated that dTOR (Drosophila target of rapamycin) is downstream and epistatic to the phosphatidylinositol 3-kinase/AKT pathway (5,16,17). However, AKT has recently been shown to negatively regulate the translation of the Elk-1 and Sap1a mRNAs independently of mTOR (18), and our prior work (19) also suggests a role for AKT in the regulation of cap-independent translation.…”
mentioning
confidence: 99%